Effects of Exercise to Improve Cardiovascular Health - Pinckard, Kelsey; Baskin, Kedryn K.; Stanford, Kristin I. (Frontiers in Cardiovascular Medicine, 2019)
Obesity is a complex disease that affects whole body metabolism and is associated with an increased risk of cardiovascular disease (CVD) and Type 2 diabetes (T2D). Physical exercise results in numerous health benefits and is an important tool to combat obesity and its co-morbidities, including cardiovascular disease. Exercise prevents both the onset and development of cardiovascular disease and is an important therapeutic tool to improve outcomes for patients with cardiovascular disease. Some benefits of exercise include enhanced mitochondrial function, restoration and improvement of vasculature, and the release of myokines from skeletal muscle that preserve or augment cardiovascular function. In this review we will discuss the mechanisms through which exercise promotes cardiovascular health.